LEGITIMACY AND RESILIENCE AS FACTORS OF DEMOCRATIC AND NON-DEMOCRATIC REGIMES' DURABILITY - Kyselov, Sergiy; Synhaievska, Dariia (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2025)
The article delves into the study of key factors that ensure the resilience, i.e., the long-term viability and stability, of different types of political regimes – both democratic and non-democratic. The main focus is on the analysis of the concepts of political legitimacy and resilience. Drawing upon the theoretical works of David Easton, Jean-Jacques Rousseau, David Held, Seymour Martin Lipset, Immanuel Kant, as well as research on resilience by David Andersen, Jørgen Møller, Lasse Rørbæk, and Svend-Erik Skaaning, the article distinguishes between legitimacy as the deep normative foundation of power (diffuse support according to Easton) and public support as situational approval of the authorities' activities (specific support). It is emphasized that legitimacy is not an exclusive feature of democracies; non-democratic regimes also require it, transforming force into right (J.-J. Rousseau) and relying on the 'customary norms' inherent in society. The Kantian distinction is introduced between autonomy of the will (self-legislating adherence to the moral law), realized under the conditions of individual freedom in democratic regimes, and heteronomy (subordination to external causes), characteristic of non-democratic regimes, where non-freedom and non-dignity facilitate complicity in 'the banality of evil'. Research shows that the resilience of democracies significantly depends on administrative capacity and bureaucratic quality, whereas the resilience of non-democratic regimes correlates with the level of tax mobilization and expenditures on coercive structures. The different sources of resilience are also overviewed: for democracies, administrative capacity and the quality of state institutions are critically important. These differences are illustrated by historical examples: President Kennedy's rejection of Operation Northwoods demonstrates the functioning of checks and balances system in a democracy, while the events surrounding the 'Ryazan sugar' operation in Russia demonstrate the commitment of a non-democratic regime to use coercive power to maintain itself. Ultimately, the study contributes to broader debates in political science about the conditions under which legitimacy translates into stability, revealing that resilience is not merely about survival, but about the quality and nature of governance itself. Special attention is paid to the dual nature of legitimacy as both a normative justification of power and a practical tool of governance, which may either constrain rulers or empower them depending on institutional and societal contexts.